An Analysis of Reference as a Grammatical Cohesive Device in the UN Secretary General Antonio Guterres' Speech in Kuwait in 2018 - Al-Khalidy, Hatmal Odeh (Jordan Journal of Modern Languages & Literatures, 2025)
This research aims to investigate the personal, demonstrative, endophora, exophora and comparative references used by the UN Secretary General Antonio Guterres. The study has applied descriptive and qualitative approach based on Halliday and Hassan (1976) to the speech of the United Nations Secretary-General. The speech, delivered on 14th February 2018 in Kuwait, was used especially for the purpose of the numerical analysis of different types of references as a sub-branch of grammatical cohesive devices. The research has studied the use of endophorics (anaphora and cataphora), personal, demonstrative, exophora, and comparatives by investigating the frequency of their occurrence. This current research finds that the demonstratives are the most frequently used by Guterres. This is followed by personal pronoun references and endophoric references respectively, while exophoics and comparatives are equally used in the speech and are the least frequent types. Keywords: Antonio Guterres, cohesive devices, comparative reference, demonstrative reference, endophora, exophora, grammatical cohesion Highlights: Demonstratives are the most frequently used by Guterres (64 times). Personal pronoun references (55 times). Endophoric references (28 times). Exophoic references (1 time only). Comparative references (1 time only).